Recent progress in understanding of hypertension - Mutig, K. (National Laboratory Astana, NAZARBAYEV UNIVERSITY, 2016)
Uncontrolled hypertension is associated with increased risk of cardiovascular morbidity and mortality in general population. Renal salt handling is essential for volume regulation and blood pressure control. The kidney-specific Na-(K)-CI cotransporters, NKCC2 and NCC, mediate salt reabsorption along the distal nephron thus determining the urinary salt excretion.
Keywords: hypertension